A single intranasal administration of AdCOVID protects against SARS-CoV-2 infection in the upper and lower respiratory tracts. Issue 6 (30th November 2022) - Schultz, Michael D.; Suschak, John J.; Botta, Davide; Silva-Sanchez, Aaron; King, R. Glenn; Detchemendy, Thomas W.; Meshram, Chetan D.; Foote, Jeremy B.; Zhou, Fen; Tipper, Jennifer L.; Zhang, Jianfeng; Harrod, Kevin S.; et al.
ABSTRACT: The coronavirus disease 2019 (COVID-19) pandemic has illustrated the critical need for effective prophylactic vaccination to prevent the spread of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Intranasal vaccination is an attractive approach for preventing COVID-19 as the nasal mucosa is the site of initial SARS-CoV-2 entry and viral replication prior to aspiration into the lungs. We previously demonstrated that a single intranasal administration of a candidate adenovirus type 5-vectored vaccine encoding the receptor-binding domain of the SARS-CoV-2 spike protein (AdCOVID) induced robust immunity in both the airway mucosa and periphery, and completely protected K18-hACE2 mice from lethal SARS-CoV-2 challenge. Here we show that a single intranasal administration of AdCOVID limits viral replication in the nasal cavity of K18-hACE2 mice. AdCOVID also induces sterilizing immunity in the lungs of mice as reflected by the absence of infectious virus. Finally, AdCOVID prevents SARS-CoV-2 induced pathological damage in the lungs of mice. These data show that AdCOVID not only limits viral replication in the respiratory tract, but it also prevents virus-induced inflammation and immunopathology following SARS-CoV-2 infection.